EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE INVESTIGASI KELOMPOK (GROUP INVESTIGATION) TERHADAP HASIL BELAJAR MATEMATIKA BERDASARKAN GAYA BELAJAR SISWA - Richardo, Rino (Edu Research, 2015)
The objectives of this research were to investigate: (1) which learning model of the Group investigation, and the direct learning results in a better learningachievement in Mathematics; (2) which students of those with the visual learning style, those with the kinesthetic learning style, and those with auditorial learning style have a better learning achievement in Mathematics; (3) interaction between GI cooperative learning model with Direct learning with learning style. This research used the quasi experimental research method with the factorial design of 2x3.